2014
DOI: 10.1007/s00520-014-2120-8
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine use and disclosure amongst Australian radiotherapy patients

Abstract: CAM use was prevalent amongst cancer patients undergoing radiotherapy, but frequently not discussed with the treating radiation oncologist. Considering the high prevalence of CAM, further resources could be justifiably directed at providing this service for cancer patients to foster a more holistic approach to their care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…44 % reported using more than 1 CM therapy. X X Hunter et al, 2014 [ 37 ] Cross sectional survey Radiotherapy patients 152 6 45.4 % CM users. Higher CM use in females & Caucasians.…”
Section: Resultsmentioning
confidence: 99%
“…44 % reported using more than 1 CM therapy. X X Hunter et al, 2014 [ 37 ] Cross sectional survey Radiotherapy patients 152 6 45.4 % CM users. Higher CM use in females & Caucasians.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to note that the use of CAM products might be associated with hazardous health risks related to their adverse effects, improper dosage or quality of the products (eg, contamination, misidentification or lack of standardisation) 9. These risks could be amplified due to the low rate of disclosure to healthcare providers for fear of their disapproval, disinterest or inability to help 10–13. Such lack of professional supervision may further expose the consumer to various risks, including adverse reactions or interactions with conventional drugs 6 14 15…”
Section: Introductionmentioning
confidence: 99%
“…Early cases are usually treated with either surgery or RT, where locally-advanced primary carcinoma of the H&N are treated with RT, often combined with chemotherapy [ 1 ]. Following the introduction of hyper-fractionation schedules of RT and technological improvements like intensity modulated RT (IMRT), higher tumor dose and reduction of some toxicity endpoints, such as xerostomia [ 2 ], can be achieved but the toxicity remains substantial [ 3 , 4 ]. In 2000, Pignon et al [ 5 ] published a three meta-analyses study, which showed that combining RT with simultaneous chemotherapy on average results in an 8 % absolute increase of the overall 2-years survival.…”
Section: Introductionmentioning
confidence: 99%